Winged celestial dancer on pillar capital at Jabreshwar temple - Ghosh, Ayan (2023)
The Jabreshwar Mahadev Temple is built in the North Indian Nagara style with an elegant shikhara rising above the garbagriha. The shikhara is embellished with carvings of musicians, lions, monkeys and elephants. The exterior wall of the sabhamandap has an arched makara torana flanked by celestial dancers on pillar capitals. These winged female figures are draped in the local Koli way of wearing the saree.